The Effect of Competency-Based Training and the Work Environment on the Performance of Non-Medical Administrative Employees at a Private Hospital in Tangerang Regency - Sapitri, Rachmawati; Sukarya, Yaya; Priyono, Agung (AGUSPATI Research Institute, 2025)
This study aims to analyze the effect of competency-based training and the work environment on the performance of non-medical administrative employees at a private hospital in Tangerang Regency, with a total population of 200. The performance of non-medical employees plays a crucial role in supporting the smooth operation of the hospital, thus requiring appropriate training and a conducive work environment. This study used a quantitative approach with a survey method. The sample consisted of 50 respondents, all non-medical administrative employees who had participated in training and worked for more than one year. Data were collected using a questionnaire, and the research instruments were tested for validity and reliability. The validity test results showed that all items in the competency-based training, work environment, and employee performance variables had correlations exceeding the r table (0.278), thus being declared valid. The reliability test using Cronbach's Alpha yielded values >0.60, thus declaring all instruments reliable. Multiple linear regression analysis showed that competency-based training had a positive and significant effect on employee performance (p = 0.010), as did the work environment (p = 0.000). A simultaneous test (F-test) showed that competency-based training and the work environment simultaneously had a positive and significant effect on employee performance with a significance level (p = 0.000). The study found that 43.8% of employee performance variables could be explained by competency-based training and the work environment, while the remaining 56.2% was explained by other variables not included in this study, such as work pressure and job satisfaction.